Emergence of multiple collective motility modes in a physical model of cell chains - Ying Zhang; Effie E. Bastounis; Calina Copos (npj Systems Biology and Applications)
Abstract Collective cell migration is central to processes like development and cancer metastasis. While mechanisms of collective motility are increasingly understood, their classification remains incomplete. Here, we study the migration of small cell chains, namely cohesive pairs. Experiments with Dictyostelium discoideum (Dd) revealed two motility modes: the individual contributor (IC) mode, where each cell generates its own traction dipole, and the supracellular (S) mode, characterized by a single dipole. Dd pairs favored the IC mode, while Madin-Darby canine kidney (MDCK) doublets predominantly used the S mode. A 2D biophysical model recapitulated many experimental observations; the IC mode emerged naturally in ameboid Dd doublets when both cells exerted similar traction stresses, while the S mode dominated with stronger leaders. Contrary to amebas, MDCK-like cell chains showed a bias towards the IC mode when increasing cell-cell adhesion. Extending the model to longer chains, we show its potential for understanding emergent migration patterns across cell types and scales.